Anitfungal and Phytochemical Screening of Carica Papaya Seed Extract - Achukwu,Ngozika,O. ,Aniobi,Charles.C. ,Isiofia,Peace,O. ,Ajare,Chidinma,A. ,Agu,Adaora,N (Sokoto Journal of Medical Laboratory Science)
Carica papaya is a plant known globally for its nutritional properties. The various part of the plant has therapeutic potential. The seed was analyzed to determine its proximate, phytochemical in-vivo activity against fungi isolates using methanol, n-hexane, ethanol and aqueous extract of the seed. The proximate analysis showed that the seed contains protein, carbohydrate, fiber, ash. The phytochemical contents tested were alkaloids, saponin, phenol, flavonoids, glycoside, tannin, anthraquinone and steroid. The in-vitro antifungal analysis activity of Carica papaya seed was determined using agar well diffusion method. The fungal isolates tested were Aspergillus niger, Candida albicans, Aspergillus flavus, Fusarium and Penicillium. All the isolates were sensitive to both extracts at different concentration. The highest zone of inhibition recorded was against Candida albicans and the least was against Fusarium 6mm. The methanol and ethanol extract had a better zone of inhibition as antifungal at the 100mg/ml than the n-hexane and aqueous extract. The seed of Carica papaya has abortifacient, emmenagogue, counter irritant and vermifuge (Singh and Ali, 2011). The seed of carica papaya has both nutritional and therapeutic benefits (Joachim et al., 2013). The seed is reported to have antibacterial and antifungal properties (Kanadi et al., 2021). Kanadi et al. (2019) in their report wrote that C. papaya seed possesses preventive measures against potassium bromated induced renal toxicity in rats.  It is of great importance to assess the nutritive and medicinal use of this plant for improved usage. Fungi causes harm to different parts of the human body such as the foot, tongue, skin, nail, cardiovascular, nervous digestive and system (He et al., 2017).  Fungal infections like candidiasis can be very severe and even fatal in immunocompromised patients (Wirth et al., 2008, Morace et al., 2014). There has been an increasing report of resistance of drugs to fungal infections due to drug abuse and wide usage of antifungal drugs broad spectrum like fluconazole, itraconazole and ketoconazole (Sheikh et al., 2018). Most antifungal agents are antifungal property and could serve as alternative antifungal agent.